SAT0616 Knee Isometric and Isokinetic Strength in Fallers and Non-Fallers with Rheumatoid Arthritis. (15th July 2016) - Clarke, C.; Smith, J.; Yates, M.; Watts, L.; Graham, K.; Pomeroy, V.; O'Neill, T.; Macgregor, A.
Abstract : Background: Muscular weakness is a cause of instability that has been reported to contribute to falling. Isokinetic and isometric dynamometry is a method of muscle assessment useful to measure the muscular strength and gives a quantification of the weakness and a comparison of strength across limbs and in reciprocal muscles. Objectives: To compare isokinetic and isometric knee flexion and extension strength between fallers and non-fallers with Rheumatoid Arthritis (RA). Methods: Sixty people with RA who gave informed consent were divided into two groups based on having a fall or not in the period of one year before evaluation, fallers (n=30, age 72.4years 15 males) and non-fallers (n=30, age 72.5 years, 16 males). Knee flexor and extensor strength was assessed using isokinetic and isometric dynamometry. Participants both limbs were tested at three fixed angular velocities isokinetically: 120°/s, 90°/s, and 60°/s and at three fixed positions isometrically, 90°, 60° and 30°. Bilateral comparison was determined by the percent deficit between left and right limbs for each participant. The ipsilateral comparison was determined between reciprocal muscles by the flexion/extension ratio. Independent t-test was used to identify significant differences between the fallers and non-fallers. The significance level was set at p<0.05 Results: 25 fallers and 30 non-fallers completed the isometric tests and 23 fallers and 28 non-fallers completed the isokinetic tests. In the bilateral comparison of the weaker and stronger limb in the fallers and non-fallers groups showed a large percentage deficit (range 22–43%) of isokinetic muscle strength between limbs in flexion and extension. Fallers had a significantly larger percentage deficit than non-fallers of isometric muscle strength between limbs in extension at 90° (p=0.02) and 60° (p=0.01). The ipsilateral comparison shows that the fallers had a significantly (p<0.05) smaller flexion/extension ratio indicating a reduced hamstring strength at all isokinetic speeds (120°/sec F:0.73, NF:0.97, 90°/sec F:0.75, NF:0.94, 60°/sec F:0.74, NF:0.90). The fallers also had a significantly (p<0.05) smaller flexion/extension ratio isometrically at 60° and 30°. Conclusions: These results demonstrate both RA fallers and RA non-fallers showed a large deficit in muscle strength between limbs. RA fallers had a significantly larger limb deficit in isometric extensor strength at 90° and 60°. The RA fallers had a significantly reduced flexion/extension ratio compared to the RA non-fallers indicating an imbalance between quadriceps and hamstring strength. Addressing the weakness in one limb and the imbalance between quadriceps and hamstrings may reduce the number of falls in this population. Disclosure of Interest: None declared